Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5194/tc-13-943-2019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CloudSat snowfall rate profiles by a comparison with in situ micro-rain radar observations in East Antarctica

Abstract: Abstract. The Antarctic continent is a vast desert and is the coldest and the most unknown area on Earth. It contains the Antarctic ice sheet, the largest continental water reservoir on Earth that could be affected by the current global warming, leading to sea level rise. The only significant supply of ice is through precipitation, which can be observed from the surface and from space. Remote-sensing observations of the coastal regions and the inner continent using CloudSat radar give an estimated rate of snow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 25 publications
(26 reference statements)
1
28
0
Order By: Relevance
“…In particular, CloudSat measured the intensity of two snowfall events (0.44 and 0.65 mm/hr) within ± 9% as compared to the precipitation gauge at KAN-B. These findings corroborate Lemonnier et al (2019), who demonstrated that CloudSat measured snowfall rates of individual events with accuracies of −13 to +22% in comparison to microrain radar instruments located at the Dumont d'Urville and Princess Elisabeth stations in Antarctica. However, at Summit, we find that POSS observed 117 more snowfall events than CloudSat.…”
Section: Accuracy Assessmentsupporting
confidence: 82%
“…In particular, CloudSat measured the intensity of two snowfall events (0.44 and 0.65 mm/hr) within ± 9% as compared to the precipitation gauge at KAN-B. These findings corroborate Lemonnier et al (2019), who demonstrated that CloudSat measured snowfall rates of individual events with accuracies of −13 to +22% in comparison to microrain radar instruments located at the Dumont d'Urville and Princess Elisabeth stations in Antarctica. However, at Summit, we find that POSS observed 117 more snowfall events than CloudSat.…”
Section: Accuracy Assessmentsupporting
confidence: 82%
“…We reconstructed snowfall on the AIS at new temporal resolutions based on the CloudSat 2C-SNOW-PROFILE dataset. Monthly AWS snow accumulation was compared with monthly CloudSat snowfall and MRR was compared with instantaneous CloudSat snowfall in the previous studies [17,18]. Unlike previous studies [17,18], daily snow accumulation and extreme snow accumulation events were compared with synoptic CloudSat snowfall.…”
Section: Introductionmentioning
confidence: 99%
“…Monthly AWS snow accumulation was compared with monthly CloudSat snowfall and MRR was compared with instantaneous CloudSat snowfall in the previous studies [17,18]. Unlike previous studies [17,18], daily snow accumulation and extreme snow accumulation events were compared with synoptic CloudSat snowfall. We also compared the CloudSat snowfall with the ERA5 snowfall to evaluate the synoptic performance of the new European Centre for Medium-Range Weather Forecasts (ECMWF) climate reanalysis dataset [32], which has now fully replaced the ERA-Interim dataset [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations